2021
DOI: 10.1002/jia2.25858
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1, open‐label study to evaluate the drug interaction between islatravir (MK‐8591) and the oral contraceptive levonorgestrel/ethinyl estradiol in healthy adult females

Abstract: Introduction: Hormonal contraceptives are among the most effective forms of reversible contraception, but many other compounds, including some antiretrovirals, have clinically meaningful drug-drug interactions (DDIs) with hormonal contraceptives. Islatravir is a novel human immunodeficiency virus nucleoside reverse transcriptase translocation inhibitor currently in clinical development for treatment and prevention of HIV infection. A phase 1 clinical trial was conducted to evaluate the DDI of islatravir and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Furthermore, a phase 1b study analyzed the impact of ISL on the pharmacokinetic profile of the NNRTI doravirine in adults without HIV infection [40] and found that the pharmacokinetic of doravirine administered alone and in combination with ISL were comparable and that doravirine did not have a meaningful impact on the pharmacokinetic of ISL. Similarly, a study of 14 healthy subjects found no clinically meaningful interaction between ISL and the investigational NNRTI MK-8507 [41]. Additionally, ISL had no clinically significant interaction when combined with dolutegravir and TDF [42].…”
Section: Drug-drug Interactionsmentioning
confidence: 96%
“…Furthermore, a phase 1b study analyzed the impact of ISL on the pharmacokinetic profile of the NNRTI doravirine in adults without HIV infection [40] and found that the pharmacokinetic of doravirine administered alone and in combination with ISL were comparable and that doravirine did not have a meaningful impact on the pharmacokinetic of ISL. Similarly, a study of 14 healthy subjects found no clinically meaningful interaction between ISL and the investigational NNRTI MK-8507 [41]. Additionally, ISL had no clinically significant interaction when combined with dolutegravir and TDF [42].…”
Section: Drug-drug Interactionsmentioning
confidence: 96%
“…A subdermal implant, islatravir (MK-8591), is novel HIV nucleoside reverse transcriptase translocation inhibitor (NRTTI), making it the first-in-class translocation inhibitor. 52 It has high TA B L E 3 Summary of select investigational products for HIV pre-exposure prophylaxis. ARV potency, a unique mechanism of action, and a prolonged plasma half-life of 48-64 h, making it an ideal option for treatment and prevention.…”
Section: Investigational Prepmentioning
confidence: 99%
“…Implants, films, and vaginal rings provide additional novel delivery options for HIV prevention. A subdermal implant, islatravir (MK‐8591), is novel HIV nucleoside reverse transcriptase translocation inhibitor (NRTTI), making it the first‐in‐class translocation inhibitor 52 . It has high ARV potency, a unique mechanism of action, and a prolonged plasma half‐life of 48–64 h, making it an ideal option for treatment and prevention.…”
Section: Pre‐exposure Prophylaxismentioning
confidence: 99%
“…Likewise, an earlier prospective, nonrandomized trial suggested that norethisterone‐based progestin‐only contraceptives exhibit increased drug levels when co‐administered with ritonavir‐boosted protease inhibitors 60 . However, not all ART medications demonstrate alterations in contraceptive hormone pharmacokinetics: a recent phase 1 trial found that the pharmacokinetics of COCs (levonorgestrel/ethinyl estradiol) were not altered with islatravir (a novel NRTI) and did not require dose adjustment 61 …”
Section: Contraceptive Options For People Living With Hivmentioning
confidence: 99%
“…60 However, not all ART medications demonstrate alterations in contraceptive hormone pharmacokinetics: a recent phase 1 trial found that the pharmacokinetics of COCs (levonorgestrel/ethinyl estradiol) were not altered with islatravir (a novel NRTI) and did not require dose adjustment. 61 Another drug-drug interaction of clinical concern is hyperkalemia when drospirenone-containing contraceptives are used along with cobicistat-containing ART regimens. 58 Currently, drospirenone-containing contraceptives are generally contraindicated in users of cobicistat-boosted protease inhibitors when an alternative or additional contraceptive method is available.…”
Section: Combined Hormonal and Progestin-only Oral Contraceptivesmentioning
confidence: 99%